PARTICIPATORY RURAL APPRAISAL IMPLEMENTATION IN IDENTIFYING PUBLIC OPEN SPACE - Megayanti, Trias; Fitria, Dian (Journal of Architectural Research and Education, 2020)
. Public open space performs an important role to enhance the quality of community living as well as being beneficial in maintaining the ecosystem. It is also having a prominent role in disaster risk management applied to densely populated settlements. Nevertheless, social awareness about the essential role and utilization of green open space is still a concern. The aim of this paper is to deliberate the result of the river banks potential analysis that serves as a green open space and communal space. This study is conducted by the Participatory Rural Appraisal (PRA) methods, which was carried out in collaboration with the local community group, to asses the potency of green open space at Nagrikaler, Purwakarta Regency, Indonesia. The result shows that community empowerment in optimizing public space, requires a critical awareness process for the local community to maintain environmental sustainability and social interaction. It is also shows the mapping of green open space at the village. The results from this study is being used as guidelines for designing green open spaces with community architecture methods based on the needs of the local community.